ANALISIS PENGARUH EFEKTIVITAS SISTEM PENILAIAN KINERJA TERHADAP MOTIVASI KERJA, KEPUASAN KERJA DAN KINERJA KARYAWAN PT COATS REJO INDONESIA - Ratih Maria Dhewi; Syamsul Ma'arif (Jurnal Manajemen & Agribisnis, 2006)
This study shows that dimension ofacceptability has the higher contribution followed by dimension of sensitivity,relevance and reliability. In contrast, dimension of practicality has thelowest contribution to motivation, work satisfaction and work performance. Furthermore,the company has not yet been able to comply with the employee's expectations ofpracticality used in conducting performance appraisal system. In other words,further evaluation of performance appraisal system emphasizing on practicalityfactors is required; keep manage and evaluate from the priority dimensionsof  acceptability, sensitivity, relevanceand reliability. These steps will lead to a condition of satisfactory to theexpectation of both the company and the employees; high work performance as aresult of highly motivated and work satisfaction employees. Keywords: effectiveness, Structural Equation Modeling, performance appraisal, motivation, employee